The Vascular Basis of the Pronator Quadratus Muscle Flap and Its Use in Clinical Cases - Binu P. Thomas; Sasi P. Kiran; Maolin Tang; Christopher R. Geddes; Steven F. Morris (Indian Journal of Plastic Surgery)
Background Pronator quadratus (PQ) is a deeply situated muscle in the forearm which may occasionally be utilized for soft-tissue reconstruction. The purpose of this anatomical and clinical study was to confirm vascular supply of PQ muscle (PQM) in order to optimize its transfer and confirm its utility in clinical situations. Methods In Part A of the anatomical study, fresh human cadavers (n = 7) were prepared with an intra-arterial injection of lead oxide and gelatin solution, and PQM and neurovascular pedicle were dissected (n = 14). In the anatomical study Part B, isolated limbs of embalmed human cadavers (n = 12) were injected with India ink-gelatin mixture and PQ were dissected. Results PQ is a type II muscle flap, with one major pedicle, the anterior interosseous (AI) vessels and two minor pedicles from the radial and ulnar vessels. The mean dimensions of the muscle were 5.5 × 5.0 × 1.0 cm3, mean pedicle length was 9.6 cm, and the mean diameter of the artery and the vein was 2.3 mm and 2.8 mm, respectively. The dorsal cutaneous perforating branch (DPB) of the artery supplied the skin over the dorsal forearm and wrist. This branch also anastomosed with the 1, 2 intercompartmental supraretinacular artery (ICSRA). Conclusion This study confirms the potential utility and vascular basis of the PQM flap and its associated cutaneous paddle. In the clinical part, two patients with nonhealing wounds exposing the median nerve and flexor tendons in the distal forearm were treated using the PQM flap with good results.